Screening of phenolic components and antimicrobial properties of Iris persica L. subsp. persica extracts by in vitro and in silico methods - Unver, Tuba; Uslu, Harun; Gurhan, Ismet; Goktas, Bunyamin (Wiley, 2024)
The tendency toward natural herbal products has increased due to the antibiotic resistance developed by microorganisms and the severe side effects of antibiotics commonly used in infectious diseases worldwide. Although antimicrobial studies have been conducted with several species of the Iris genus, this study is the first in the literature to be performed with Iris persica L. subsp. persica aqueous and methanol extracts. In this study, the phenolic content of I. persica was determined by LC-MS/MS analysis, the in vitro antimicrobial activity of I. persica aqueous and methanol extracts was examined, and this study was supported by in silico analysis. Consequently, methanol and aqueous extracts were observed to have inhibitory effects against all tested microorganisms except Candida krusei. Although the MIC values of aqueous extract and methanol extract against Staphylococcus aureus and Klebsiella pneumoniae are the same (22.5 and 11.25 mg/mL, respectively), the inhibitory effect of aqueous extract is generally more potent (MIC value is 11.25 mg/mL for Candida parapsilosis and other bacterial species, and 90 mg/mL for Candida albicans and Candida tropicalis) than that of methanol extract. In silico results showed that hydroxybenzaldeyde, vanillin, resveratrol, isoquercitrin, kaempferol-3-glucoside, fisetin, and luteolin were more prone to antifungal activity. Hence, shikimic, gallic, protocatechuic, vanillic, caffeic, o-coumaric, trans-ferulic, sinapic acids, and hesperidin were more prone to antibacterial activity. In vitro and in silico results show that the antibacterial activity of our extracts may be higher than the antifungal activity. This preliminary study indicates the anti-infective potential of I. persica extracts and their usability in medicine and pharmacology.
Keywords: antimicrobial activity; herbal medicine; Iris persica; molecular docking; phenolic contents